The effect of food environments on fruit and vegetable intake as modified by time spent at home: a cross-sectional study. Issue 6 (4th June 2015) - Chum, Antony; Farrell, Eddie; Vaivada, Tyler; Labetski, Anna; Bohnert, Arianne; Selvaratnam, Inthuja; Larsen, Kristian; Pinter, Theresa; O'Campo, Patricia
Abstract : Objective: There is a growing body of research that investigates how the residential neighbourhood context relates to individual diet. However, previous studies ignore participants' time spent in the residential environment and this may be a problem because time-use studies show that adults' time-use pattern can significantly vary. To better understand the role of exposure duration, we designed a study to examine 'time spent at home' as a moderator to the residential food environment-diet association. Design: Cross-sectional observational study. Settings: City of Toronto, Ontario, Canada. Participants: 2411 adults aged 25–65. Primary outcome measure: Frequency of vegetable and fruit intake (VFI) per day. Results: To examine how time spent at home may moderate the relationship between residential food environment and VFI, the full sample was split into three equal subgroups—short, medium and long duration spent at home. We detected significant associations between density of food stores in the residential food environment and VFI for subgroups that spend medium and long durations at home (ie, spending a mean of 8.0 and 12.3 h at home, respectively—not including sleep time), but no associations exist for people who spend the lowest amount of time at home (mean=4.7 h). Also, no associations were detected in analyses using the full sample. Conclusions: Our study is the first to demonstrate that time spent at home may be an important variable to identify hidden population patterns regarding VFI. Time spent at home can impact the association between the residential food environment and individual VFI.